Determinants of Debt Rescheduling in Pakistan (The Pakistan Development Review, 2001)
Pakistan’s total debt has reached to 115 percent of GDP in 2001 [Pakistan (2001)]; per capita debt exceeded per capita GDP. The outstanding stock of public debt was roughly 400 percent of government revenue in 1980 and it increased to 624 percent by mid-2000 [Pakistan (2001)]. It is the only country in South Asia, classified as “severely indebted low-income country” by the World Bank (2001). Debt servicing is more problematic than debt. It has been 2.5 percent of GNP during seventies and increased to 3.5 percent of GNP during eighties. In 2001, debt servicing consumes more than seventy percent government revenue and leaves less than thirty percent for every thing else [The News (2001)]. This increase in debt and debt servicing has affected creditworthiness of the country and raised the concern about its future growth prospects. The deterioration in all the indicators, like debtexport ratio, debt-GDP ratio, debt servicing to GDP ratio etc. raised the risk of default and increased vulnerability of the country to external and internal shocks. One possible way out is the rescheduling of debt to minimise total loss to creditor countries as well as subside the burden of debtor country. Pakistan’s debt has been rescheduled many times during the last thirty years.